Wisdom of Chinggis Khaan - Ch. Batyn, Gan-Ulzii (Studia Philosophiae Et Juris, 2022)
Philosophy differs from the sciences, on the one hand, by hidden power, magical beliefs (magic), and on the other hand, the ideas of mysticism, and on the other hand, the real material experience of the living world is worshipped with foresight, intuition, emotional power and meaning. The article states that during the reign of Genghis Khagan, philosophy was formed in a form close to European, in terms of the content of naturalistic nomadic life wisdom. Genghis Hagan could... Чингис хааны мэргэн ухаан Хураангуй: Философийг шинжлэх ухаануудаас өөрөөр нэг талаас, далдын хүч, ид шидийн итгэл үнэмшил (magic), агийн ёс (mysticism)-ны санаалаг юмс нөгөө талаас, амьдрах ертөнцийн бодит материаллаг туршлагатай шүтэн барилдуулж урьдах ухаан, урьдаас мэдрэх зөн билиг, сэтгэл хөдлөлийн хүч, утгын тайлал, мэдэгдэхүүний билгийн ухаарлын чинад эргэн хянах арга зүй болгон ашиглаж байгаад судалгааны шинэлэг тал оршино Tүлхүүр үгс: мэргэн ухаан, сэцлэх, мэдэгдэхүүн, бичиг, уоьдах, найраг